Proceedings of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition monothematic conference, 2020: "Acute liver failure in children": treatment and directions for future research - Zellos, Aglaia; Debray, Dominique; Indolfi, Giuseppe; Czubkowski, Piotr; Samyn, Marianne; Hadzic, Nedim; Gupte, Girish; Fischler, Björn; Smets, Françoise; Clément de Cléty, Stéphan; Grenda, Ryszard; Mozer, Yael; et al. (Journal of pediatric gastroenterology and nutrition, 2022)
Objectives: The Hepatology Committee of the European Society for Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) aims to educate pediatric gastroenterologists, members of ESPGHAN and professionals from other specialties promoting an exchange of clinical expertise in the field of pediatric hepatology. - Methods: The 2020 single topic ESPGHAN monothematic 3-day conference on pediatric liver disease, was organized in Athens, Greece and was entitled “ Acute Liver Failure” (ALF). ALF is a devastating disease with high mortality and in a considerable fraction of patients, the cause remains unresolved. As knowledge in diagnosis and treatment of ALF in infants and children has increased in the past decades, the objective was to update physicians in the field with developments in medical therapy and indications for liver transplantation (LT) and to identify areas for future research in clinical and neurocognitive outcomes in ALF. - Results: We recently reported the epidemiology, diagnosis, and initial intensive care management issues in separate manuscript. Herewith we report on the medical treatment, clinical lessons arising from pediatric studies, nutritional and renal replacement therapy (RRT), indications and contraindications for LT, neurocognitive outcomes, new techniques used as bridging to LT, and areas for future research. Oral presentations by experts in various fields are summarized highlighting key learning points. - Conclusions: The current report summarizes the current insights in medical treatment of pediatric ALF and the directions for future research.
Date: Oct 28, 2021
Gesehen am 12.04.2022